Cooperação das áreas funcionais no processo de desenvolvimento de máquinas agrícolas - Facco, Giuliani (2016)
The competitive capacity within a certain sector, is the determining factor in determining whether a company has the potential to continue in the market or not. In this sense, the agricultural machinery sector, seeking to remain competitive, seeks best practices for the organization and management of its product development processes. These well-defined and managed processes can help sustain a company's competitiveness. The Product Development Process is approached in this work taking into account its multidisciplinarity, considering the importance of the participation of several functional areas for the management and the efficient performance of the process. Thus, the objective of this dissertation is to identify and evaluate the cooperation of the functional areas in agricultural machinery development processes. To obtain the objective, a detailed study was carried out on the industrial segment of agricultural machinery, especially in the methodologies used for the development of its products, in order to know the intervening factors of these processes in a broad and detailed manner. We selected the Reference Model for the Agricultural Machinery Development Process as a starting point, where the functional areas described in this model were used to analyze two other models of the product development process large multinational companies, agricultural machinery manufacturers. In order to identify the cooperation of the functional areas throughout the phases and activities of the studied models, structures were developed in the form of electronic spreadsheets that sought to intersect the activities and areas of each model, making it possible to identify the level of participation of the functional areas in each phase the process. With the study of the phases and activities of the models, it was observed that it is necessary the cooperation of specific knowledge from certain functional areas for the development of agricultural machinery, making these activities be performed by several functional areas, giving agility to the process and thus collaborating to meet deadlines, so that the costs of manufacturing comply with the estimate in the project and so that the quality of the final product is as expected.